The impact of age-specific minimum wages on youth employment and education: A regression discontinuity analysis - Meltem Dayioglu; Muserref Kucukbayrak; Semih Tumen (Global Labor Organization (GLO), 2021)
We exploit an age-specific minimum wage rule - which sets a lower minimum wage for workers of age 15 than the adult minimum wage paid to workers of age 16 and above - and its abolition to estimate the causal effect of a minimum wage increase on youth employment and education in Turkey. Using a regression discontinuity design in tandem with a difference-in-discontinuities analysis, we find that increasing the minimum wage reduces the employment probability of young males by 2.5-3.1 percentage points. We also document that, initially, the minimum wage increase does not lead to a major change in high school enrollment, while the likelihood of transitioning into "neither in employment nor in education and training" (NEET) category notably increases. However, in the medium term, the NEET effect is transitory; school enrollment increases over time and absorbs the negative employment effect. We argue that policy effects have mostly been driven by demand-side forces rather than supply side.
Keywords: J21; J24; J31; J38; 330; Age-specific minimum wages; youth employment; education; regression discontinuity design